Implementation of Measurement System Analysis to Reduce Measurement Process Failures on Part Reinf BK6 - Fredy Sumasto; Yesaya Abdi Nugroho; B. Handoko Purwojatmiko; Mohammad Wirandi; Febriza Imansuri; Siti Aisyah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
This study aims to reduce the failure of the measurement process on Part Reinf BK6 in the automotive industry which prioritizes accuracy and precision in the process to maintain product quality and customer satisfaction. This study used the measurement system analysis (MSA) method to analyze the Gage R&R on a measurement system, with 2 operators and 10 parts measured with 3 repetitions. The MSA results before improvement showed a Total Gage R&R of 67.80% with a repeatability value of 0.98% and a reproducibility value of 66.82%. The result indicated that the measurement system needs to be improved because the Gage R&R is still above 30%. After improving the measurement process by adding the Go No Go pin as an additional tool, the MSA results show the Total Gage R&R value after the improvement is made to 10.11% with repeatability and reproducibility values of 10.11% and 0% respectively. Based on the results of the study, it can be concluded that the improvements made have a significant effect on the measurement system on Part Reinf BK6. This will improve accuracy and precision in the measurement process, maintain product quality, and increase customer satisfaction. Therefore, improving the measurement system is very important in the automotive industry.